Phytoremediation Ability of Ornamental Plants Celosia argantea L. and Mirabilis jalappa L. in Plumbum (Pb) Contaminated Soil - Juhriah; Dian Islamiah; Muh. Ruslan Umar (Jurusan Biologi Universitas Negeri Makassar, 2023)
Plumbum or lead is a type of heavy metal that is dangerous if it has exceeded the threshold of 0.07 μg/g based onthe National Standardization Agency SNI 2004. This type of heavy metal is found in nature such as in soil, water,and air. The purpose of the study was to determine the phytoremediation ability of two types of ornamental plants,namely Celosia argentea L. and Mirabilis jalappa L., against Plumbum (Pb) metal in soil. The growth parametersobserved consisted of plant height, plant stem diameter, number of leaves, leaf length, and leaf width. The ICPMS(Inductively coupled plasma-mass spectrometry) was used to analyze the plumbum (Pb) content in soil andplants. The results ofinitial soil analysis prior to the plant planting process (phytoremediation) were 103.17 μg/gwhich had exceeded the predetermined threshold. The result of the analysis after phytoremediation of Celosiaargentea L. showed plumbum (Pb) content of 49.685 μg/g in soil and 1,9548 μg/g in plants. Similarly, the analysisof Ph content after phytoremediation of Mirabilis jalappa L. was 47.802 μg/g in soil and 5.3077 μg/g in plants.Based on biomass calculation of Celosia argentea L. and Mirabilis jalappa L., the obtained Plumbum (Pb) contentwas 18.84% and 27.85%, respectively. The percentage of Pb removal of Celosia argentea L. was 51.842%, whileMirabilis jalappa L. was 53.667%. The efficiency of Pb absorption of Celosia argentea L. and Mirabilis jalappaL. was 1.895% and 5.145%, respectively. In conclusion, Ornamental plants Celosia argentea L., and Mirabilisjalappa L., are able to act as phytoremediation agents for Plumbum (Pb) metal that pollutes the soil as evidencedby the decrease in Pb levels in the soil after the phytoremediation process.